Associations Between Depressive Symptoms and Physical Activity Intensity in an Older Adult Population During COVID-19 Lockdown - Lage, Ana; Carrapatoso, Susana; Sampaio de Queiroz Neto, Elzier; Gomes, Sérgio; Soares-Miranda, Luísa; Bohn, Lucimere (Frontiers in Psychology, 2021)
Introduction: COVID-19 pandemic led to the implementation of physical-social distancing measures - including self-isolation, home confinement and quarantine around the world, with psychological consequences such as depression. Older adults are especially likely to develop depressive symptomatology. This study aims to investigate the association between physical activity intensities and sedentary behavior with depression levels among previously active older adults during COVID-19 lockdown. Methods: 1,123 physically active older Brazilian adults (67.68±5.91 years, 91.00% female) were interviewed by telephone in regard to sociodemographic, general health status, depression (GDS-15) and physical activity (IPAQ-SV) after being home confined for 11.59±2.42 weeks. Participants were also asked to self-report changes in their physical activity levels and time spent sitting. Descriptive statistics (mean, frequencies), between groups comparisons (t-teste and chi-square) and hierarchical regression analysis were used. Results: 83.80% of older adults self-reported a decrease in daily physical activity levels and 73.90% increased sitting time. Overall, depressive symptoms were observed in 30.40%, and 20.80% met physical activity recommendations. Daily moderate (β=-0.174; 95%CI= -0.026; -0.012) and moderate-to-vigorous (β = -0.183; 95%CI=-0.023;0.011), physical activity intensities were negatively associated with depression score explaining 2.6 and 2.9% of depression variability, respectively, after adjusting for age, gender, education level, body mass index and polypharmacy. Daily walking and sitting time were not associated with depression score (p>0.05). Conclusion: Results provide empiric suggestion supporting moderate to vigorous physical activity as a way to reduce depressive levels among older adults during COVID-19 confinement. Supervised home-based exercise programs, specifically designed for older adults might be an important strategy to maintain and improve older adult’s mental health.